After 1 year, a bank account contains $7,746.90. After 2 years, the same account contains $7,901.84. Assuming no deposits or withdrawals are made, which equation can be used to find y, the amount of money in the account after x years? (Round money values to the nearest penny.)

Answers

Answer 1
Answer: These are the choice given. I'll just substitute x with 1 and 2 to see if the amount corresponds to the given amount.
A.    y = 7591.96(1.02)x
  y = 7,591.96(1.02)¹ = 7,743.80 
  y = 7,591.96(1.02)² = 7,898.68

B.   
y = 7591.96(0.02)x
y = 7,591.96(0.02)¹ = 151.84
y =7,591.96(0.02)² = 3.04

C.   
y = 7595(1.02)x    THIS IS THE CORRECT EQUATION.
y = 7,595(1.02)¹ = 7,746.90
y = 7,595(1.02)² = 7,901.84

D.   
y = 7595(0.02)x
 

Related Questions

At one factory the ratio of defective light bulbs produced to total light bulbs produced is about 3:500. How many light bulbs are expected to be defective when 12,000 are produced
Solve for the indicated variable X/y=x-8 for x
Today the coast of a gallon of gas is $2.65. Every week for the next 10 weeks, it will increase by $0.05.a gallon. If you wrote a linear equation to model this situation,what would the slope be?
A specific aircraft can ascend 1,635 meters in 15 seconds.What is the rate of ascent?
Jesse drives to work. The distance Jesse’s car travels (d) on a number of gallons of gas (g) is given by the equation d = 15g. The constant of proportionality in terms of distance traveled per gallon of gas is?

What is 76/100 simplified

Answers

Find the highest common factor between 76 and 100.
Factors of 76: 1, 2, 4, 19, 38, 76
Factors of 100: 1, 2, 4, 5, 10, 20, 50, 100

The highest common factor is 4. Divide 76 and 100 by 4.

(76)/(100) =  (19)/(25)

(pleaseeee please help me D: I've been trying to figure this out all day)

Answers


OK.  Relax, settle down, don't worry.

We're in luck here.  The shape hasn't been rotated, or swelled up
or shrunk.  It's still exactly the same size and shape, and in the same
position.  It's only been moved, from here to there.  All you really
have to do is look at one point, and figure out how that point moved,
and all the other points moved exactly the same ... same distance,
in the same direction.

When I looked at this, I worked with point-D.  But now I think
point-B may be a little easier to work with.

-- What's the 'x'-value (left/right) of point-B before it moves ?
    It's right on the y-axis, so its x-value is zero.

-- What's the 'x' value of point-B', after the move ?
    Look at the light light line that B' is on, follow it down,
    and you see that the x-value of point-B' is  6 .

-- The x-value of point-B moved from  x=0  to  x=6.
    If you look at just the x-value of any other point on the shape,
    you'll see that every point moved 6 units to the right.
    Every 'x'-value became 6 units bigger after the move.
       x --> x+6

===================
 
-- What's the 'y'-value (up/down) of point-B before it moves ?
    It's in the middle between the 2 and the 4, so its y-value is 3.

-- What's the 'y' value of point-B', after the move ?
    Look at the light light line that B' is sitting on, follow it left,
    and you see that the y-value of point-B' is  8 .

-- The y-value of point-B moved from  y=3  to  y=8.
    If you look at just the y-value of any other point on the shape,
    you'll see that every point moved 5 units UP.
    Every 'y'-value became 5 units bigger after the move.
       y --> y+5

Look for a choice that says what we found.
The second choice says it.

in 2004, 34.2 million accountants e-filed income tax returns. this was 114% of the number who filed in 2003. Find the number of accountants who e-filed income tax returns in 2003

Answers

Answer:

30 million accountabts

Step-by-step explanation:

To get the number of accountant that refilled in 2003, 100/114 X 34.2 = 30

Find one percent by dividing it by 100, then multiply it by 114 and theres your answer. 

If f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (g – f)(3)

Answers

For this case we have the following functions:
 f (x) = 4 - x ^ 2 g (x) = 6x
 The first thing we must do is subtract both functions.
 We have then:
 (g - f) (x) = g (x) - f (x)
 Substituting values we have:
 (g - f) (x) = (6x) - (4 - x ^ 2)
 Rewriting we have:
 (g - f) (x) = x ^ 2 + 6x - 4
 Then, we evaluate the function for x = 3.
 We have then:
 (g - f) (3) = 3 ^ 2 + 6 (3) - 4
 Rewriting:
 (g - f) (3) = 9 + 18 - 4 (g - f) (3) = 23
 Answer:
 
An expression that is equivalent to (g - f) (3) is:
 
(g - f) (3) = 23

Answer:

(g-f)(3)=23

Step-by-step explanation:

Given : f(x) = 4 -x^2 and g(x) = 6x

To find : The value of (g -f)(3)

Solution :

First we find the value of (g-f)

(g-f)(x)= g(x)-f(x)

(g-f)(x)=6x-(4-x^2)

(g-f)(x)=6x-4+x^2

Now, put the value of x=3

(g-f)(3)=6(3)-4+(3)^2

(g-f)(3)=18-4+9

(g-f)(3)=23

Therefore,(g-f)(3)=23

Write the following expression without negative exponents and without parentheses. 5x^-1

Answers

The written form of the expression without negative exponents and without parentheses is; 5/x.

What is the writing form of the expression without exponents and without parentheses?

It follows from the task content that the expression can be written without parentheses and without exponents as follows;

5x-¹

= 5 × (1/x)

= 5/x

Ultimately, the written form of the expression without negative exponents and without parentheses is; 5/x.

Read more on indices;

brainly.com/question/170984

#SPJ1

a money bag contains ten 5-dollar notes and thirty 10-dollar notes. if a note is randomly selected from the bag, what is the probability of a 5-dollar note being selected?

Answers

Total no. of notes = 10+30 =40
5 dollars note = 10

probability = 10/40 =1/4
$67 answer from my oppinon